CONTRIBUTION OF THE KASHKADARYA REGIONAL MUSICAL DRAMA THEATER TO THE RISE OF THE CULTURAL AND SPIRITUAL LIFE OF THE POPULATION - Sevara Akhmadova (Web of Journals Publishing, 2025)
This article discusses the analysis of the activities and activities of musical drama theaters in Kashkadarya region during the years of independence.
Keywords: Spiritual and educational events, institution, community club, musical drama theater, ensemble, amphitheater, international festival, performance.